Ronald Hutton, Witches, Druids and King Arthur - Clifton, Chas S (Pomegranate, 2007)
Ronald Hutton, Witches, Druids and King Arthur (London: Hambledon and London, 2003), xviii + 320 pp., £19.95 (cloth).